Immersive learning technology for ensuring quality education: Ukrainian university case - Volodymyr O. Liubchak; Yurii O. Zuban; Artem E. Artyukhov (Academy of Cognitive and Natural Sciences, 2022)
The article considers the problem of using immersive learning in the educational and scientific activities of the university. Literature survey revealed that there is a need for an integrated approach for introduction of immersive learning at the university. It involves the creation of a specialized laboratory of virtual and augmented reality with appropriate technical equipment, introduction of immersive learning methodology in university educational programs, development of software and hardware solutions for immersive learning, and research on the immersive learning effectiveness. We present the description of a specialized university department acting as a developer of software products for immersive learning. We show original developments in the field of immersive education for exact sciences and arts and humanities students. The article describes products that are designed to fulfill the third university mission: to ensure the citizens well-being. We propose "immersive institute" model which can be implemented both at the level of the university in general and at the level of its educational and scientific departments.